Hubungan antara Durasi Penggunaan Komputer dengan Kelelahan Mata pada Pegawai Bank BPD Cabang Utama Denpasar - Ni Made Adinda Sadhana Pramadani; Ni Wayan Rusni; Ni Luh Putu Eka Kartika Sari (Aesculapius Medical Journal, 2024)
[Correlation between Duration of Computer Use and Eye Fatigue in Employees of BPD Bank Main Branch Denpasar] Eye fatigue is a condition when the eye muscles are overworked beyond their capacity, especially when looking at close objects for a long time. According to data from the World Health Organization (WHO), the incidence of eye fatigue in the world ranges from 40% to 90%. One activity that often causes eyestrain is computer use. This condition can be affected by individual and environmental factors, and will induce the symptoms such as headaches, blurry vision, sore eyes, and other related symptoms. The purpose of this research is to investigate the correlation between the duration of computer use and eye fatigue among the employees of the BPD Bank Main Branch in Denpasar. This research was held from November 2022 until February 2023. The method used for this research was the cross-sectional analytic method. Purposive sampling was used to collect samples, and 88 samples were obtained from employees of the BPD Bank Main Branch in Denpasar. The data collection that used was the Visual Fatigue Index (VFI) questionnaire. The data were analyzed using a chi-square test (p < 0.05). The result showed that the prevalence of computer use duration was â‰¤ 4 hours (12,5%) and > 4 hours (87,5%). The prevalence of eye fatigue was 67%. The chi-square test results obtained a p-value = 0.021, indicating a significant correlation between the duration of computer use and eye fatigue in employees of the BPD Bank Main Branch in Denpasar. Based on the results obtained, the company needs to conduct an evaluation regarding the duration of work to minimize eye fatigue and improve working comfort for employees.